The mediating impact of stickiness and loyalty on word-of-mouth promotion of retail websites: a consumer perspective. Issue 9 (19th August 2014) - Roy, Sanjit Kumar; Lassar, Walfried M.; Butaney, Gul
Abstract : Purpose: The role of Word-of-Mouth (WOM) in influencing consumer behaviour is documented in literature. However, despite its growing importance, research on the antecedents of WOM in the e-retail context is sparse. The purpose of the study is to develop and empirically test a model which examines the relationship between e-servicescape dimensions, website quality dimensions, website stickiness, website loyalty and WOM. Design/methodology/approach: Data was collected by circulating the questionnaire using an online survey from the graduate and undergraduate students enrolled in a large university in the Northeast, U.S.A. Out of 660 questionnaires distributed, 509 were usable. Data was analysed using confirmatory factor analysis and structural equation modeling. Findings: Results show that website stickiness and website loyalty are two different constructs which form the immediate antecedents of WOM. Results also show the indirect effects of e-servicescape and website quality dimensions on WOM. Practical implications: The findings of the study provides a better understanding of the factors likely to influence the word-of-mouth behaviour of e-retail store customers. Findings also provide valuable insights into the factors which managers need to focus to make their e-retail website increasingly stickier. Originality/value: The contribution of the paper lies in eliciting the differences between stickiness to- and loyalty to- retail websites and extending the research on e-servicescapes.